A rare cause of epileptic encephalopathy: a beta-propeller protein associated neurodegeneration case with a new mutation and literature review - Özgün, Nezir; Özer, Leyla; Yaramış, Ahmet (The Turkish Journal of Pediatrics, 2020)
In this report, detailed clinical features of a female patient and a new mutation that was not previously identified in the WD repeat-containing protein 45 (WDR45) gene are presented in order to contribute to the information in the literature on the phenotype as well as genotype of Beta-Propeller Protein Associated Neurodegeneration. Whole Exome Sequencing (WES) analysis was done since etiology could not be determined. Our case was admitted to the hospital due to epilepsy, growth retardation and autism. Her family history was unremarkable except consanguineous marriage. She had tonic seizures twice at the age of 7 and 12 months and had continual seizures after 16 months. At the time, electroencephalography and brain MRI were performed twice were determined to be normal. Brain MRI Spectroscopy was also found to be normal at 35 months of age. Metabolic screening tests (acyl carnitine profile, urine organic acids, plasma amino acids, a very long chain fatty acid profile, etc.) were also normal. Genetic screening of the epilepsy panel for epileptic encephalopathies was negative. WES analysis revealed heterozygous previously unreported variant in intron 6 of the WDR45 gene, c.344+5G > A. In conclusion; Beta-Propeller Protein Associated Neurodegeneration should be considered as an option in the diagnosis of female patients with clinical findings of epilepsy, growth retardation and autism, with unspecified etiology.
Keywords: WDR45 gene mutation; beta-propeller protein associated neurodegeneration; epileptic encephalopathy